Case reportPyoderma gangrenosum in a patient with common variable primary immunodeficiency - Bergler-Czop, Beata; Brzezińska-Wcisło, Ligia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Pyoderma gangrenosum is a rare inflammatory skin condition that is associated with systemic inflammatory diseases. It is characterised by the presence of well-secluded, painful ulcerations, often located on the lower limbs. Similarly as in the case of acne inversa, patients’ markers of the inflammatory process are elevated; including OB, C-reactive protein and leukocytosis. The aetiology takes into account an over-reactive inflammatory response to various factors (presence of the so-called pathergy symptom). Common variable primary immunodeficiency (CVID) is a disease that is rather often recognized and affects about 1/10,000-100,000 individuals. It is a heterogeneous group of disorders of combined B-and T-cell dysfunction. The case is described of a 22-year-old man with pyoderma gangrenosum that coexisted with CVID.